Trends in the work profession of BABC graduates, SY 2001-2004 - Acosta, Meryll Joyce; Rojo, Rea Ann.; Yulo, Novy Katherine (2004.)
This study was conducted to find out the trends or patterns in the work profession of BA Broadcast Communication graduates from school years 2001-2002, 2002-2003, and 2003-2004 using sex and major field as variables. It also aims to find out what other jobs BA BC graduates have, what factors affected them, and how satisfied are they with their jobs., This study was conducted during the first semester of the school year 2004-2005. Respondents chosen for this study were 140 graduates of BA BC from school years 2001-2004. However, only 39 were able to reply. The locale of the study includes various places in the Philippines, mostly Metro Manila City, and Iloilo Province. The research design used in this study is descriptive.Results of the study show that majority of BABC do not end up in the media. Those who were able to get into broadcast-related jobs do not plan to stay for good in their present jobs. On the other hand, those who did not get into broadcast- related jobs plan to pursue these kinds of jobs. the study also shows that most BA BC graduates within the school years are moderately satisfied with their present jobs.
Thesis, Undergraduate - UPV-CAS-Humanities.
Keywords: Work Profession -- BA Community Development